Circadian clock-gastrointestinal peptide interaction in peripheral tissues and the brain. Issue 6 (December 2017) - Landgraf, Dominic; Neumann, Anne-Marie; Oster, Henrik
Abstract : Food intake and sleep are two mutually exclusive behaviors and both are normally confined to opposing phases of the diurnal cycle. The temporal coordination of behavior and physiology along the 24-h day–night cycle is organized by a network of circadian clocks that orchestrate transcriptional programs controlling cellular physiology. Many of the peptide hormones of the gastrointestinal tract are not only secreted in a circadian fashion, they can also affect circadian clock function in peripheral metabolic tissues and the brain, thus providing metabolic feedback to metabolic and neurobehavioral circuits. In this review, we summarize the current knowledge on this gastrointestinal peptide crosstalk and its potential role in the coordination of nutrition and the maintenance of metabolic homeostasis.